THE EFFECT OF COMPENSATION, JOB SATISFACTION AND MOTIVATION ON EMPLOYEE PERFORMANCE AT PT LAUT TIMUR UTAMA, ARU ISLANDS - Nussy, Trudy Maryona (UTSAHA: Journal of Entrepreneurship, 2023)
Human resources have a crucial role. The existence of human resources has great potential in conducting company activities and their abilities can be maximised. Human resource management at PT Laut Timur Utama, Aru Islands always strives to improve employee performance in order to create efficient company productivity in the production process so as to reduce production costs and produce products at a low cost and affordable in the market. Many factors can affect the employee performance in the company, such as compensation, job satisfaction and motivation factors. Therefore, this research is conducted to determine the effect of compensation, job satisfaction and motivation on the employee performance at PT Laut Timur Utama, Aru Islands whether partial or simultaneous. The approach used in this research is quantitative with 40 respondents. In addition, the analysis model used is Multiple Linear Regression to determine the effect of independent variable on the dependent variable. Based on the results of the research, it indicates that compensation, job satisfaction and motivation have a significant effect both partially and simultaneously on employee performance of PT Laut Timur Utama, Aru Islands.